Integrated Transcriptome and Metabolome Analyses Reveal the Anthocyanin Biosynthesis Pathway in AmRosea1 Overexpression 84K Poplar - Yan, Huiling; Zhang, Xinxin; Li, Xiang; Wang, Xuelai; Li, Hanxi; Zhao, Qiushuang; Yin, Peng; Guo, Ruixue; Pei, Xiaona; Hu, Xiaoqing; Han, Rui; Zhao, Xiyang (Frontiers in Bioengineering and Biotechnology, 2022)
Populus alba × P. tremula var. glandulosa (84 K poplar) is model material with excellent genetic engineering resource and ornamental value. In our study, AmRosea1 (Antirrhinum majus) was overexpressed in 84K poplar, and the transgenic 84K poplar with high content of anthocyanin exhibited red pigmentation leaves, stems and whole plants. The transcriptome analysis between wild type (WT) and AmRosea1 overexpression transgenic 84K poplar (AM) showed that 170 differentially expressed genes (DEGs) (86 up-regulated and 84 down-regulated) were found in AM, and some DEGs were involved in flavone and flavonol biosynthesis, flavonoid biosynthesis and anthocyanin biosynthesis. The metabolome analysis of WT and AM showed that 13 anthocyanins-related differentially accumulated metabolites (DAMs) were detected in AM. The correlation analysis between DEGs and DAMs was performed, and the results revealed that 18 DEGs, including 11 MYB genes, 2 BZ1 genes, one FG2 gene, one ANS gene, and 3 IF7MAT genes, were negatively or positively correlated with 13 DAMs. The phylogenetic analysis demonstrated that there was high homology between AmRosea1 and PagMYB113, and MYB113 co-expressed with BZ1, ANS and DFR directly. Our results elucidated the molecular mechanism of plant color change mediated by anthocyanin biosynthesis pathway, which laid the foundation for the development and utilization of colorful woody plant.